The cosmic spacetime - Melia, Fulvio (Boca Raton, FL : CRC Press, 2021)
The growth of cosmology into a precision science represents one of the most remarkable stories of the past century. Much has been written chronicling this development, but rarely has any ofit focused on the most critical element of this workthe cosmic spacetime itself. Addressing this lacuna is the principal focus of this book, documenting the growing body of evidence compelling usnot only to use this famous solution to Einstein's equations in order to refine the current paradigm, butto probe its foundation at a much deeper level. Its excursion from the smallest to largest possible scales insightfully reveals an emerging link between the Universe we behold and the established tenets of our most fundamental physical theories. Key Features: Uncovers the critical link between the Local Flatness Theorem in general relativity and the symmetries informing the spacetime's metric coefficients Develops a physical explanation for some of the most unpalatable coincidences in cosmology Provides a sober assessment of the horizon problems precluding our full understanding of the early Universe Reveals a possible explanation for the origin of rest-mass energy in Einstein's theory In spite of its technical layout, this book does not shy away from introducing the principal players who have made the most enduring contributions to this field. Anyone with a graduate level foundation in physics and astronomy will be able to easily follow its contents.
OCLC-licensed vendor bibliographic record.
Keywords: Space and time; Cosmology; SCIENCE / Cosmology; SCIENCE / Astrophysics & Space Science